Role of M3 muscarinic receptor in regulation of immunity to infectious pathogens - Vira, Alykhan (Department of Clinical Laboratory Sciences, 2015)
During the last decade, cholinergic signaling via acetylcholine and its receptors has emerged as an important regulator of immunity. Acetylcholine binds to and signals through two types of receptors; nicotinic and muscarinic receptors. Studies have shown that signaling through nicotinic receptors, particularly the Î±7 subtype on macrophages has potent anti-inflammatory effects. However, the role for muscarinic receptor has not yet been conclusively characterized. In this study, we demonstrate that M3 muscarinic receptor subtype is required for optimal protective immunity to two pathogens; the nematode Nippostrongylus brasiliensis and the bacterium Salmonella enterica sp. Tyhpimurium. M3R deficient mice (M3R-/-) were susceptible to infection with N.brasiliensis with decreased production of the protective cytokine IL-13. Furthermore, stimulation of lymphocytes with muscarinic agonists enhanced TH2 cytokine production in an M3R dependent manner.